Load-strain model for concrete-filled double-skin circular FRP tubes under axial compression. (15th February 2019) - Li, Y.L.; Zhao, X.L.; Singh Raman, R.K.
Highlights: A constitutive model is developed for FRP-confined seawater and sea sand concrete. A dilation model for hoop-axial strain of concrete-filled double-skin FRP tubes. The buckling of inner FRP tube is predicted by maximum strain criteria. Load-strain model is developed for concrete-filled double-skin FRP tubes. Abstract: Concrete-filled double-skin FRP tubes (CFDST) are increasingly attracting researchers' interests due to the advantages of their reduced self-weight and higher bending stiffness than fully filled tubes. However, the structural behaviour of CFDST, especially the non-uniform confinement in annular concrete, has not ever been well addressed. This paper presents an analytic study on axial compressed circular stub CFDST with FRP wrap/tube as outer tube and steel/FRP as inner tube. Based on existing studies on actively confined concrete, a constitutive model for non-uniformly FRP-confined concrete is developed in this paper. The dilation model for concrete fully filled FRP tubes is modified to account for the effects of void ratio so that the hoop-axial strain curve of CFDST could be reasonably predicted. Behaviours of steel and FRP tubes in CFDST are investigated and proper stress-strain models are proposed to estimate the loads shared by tubes. The stress state in annular concrete is theoretically studied by dividing the cross-section into multiple circular layers. Finally, an analysis-oriented load-strain model, which accounts for the non-uniform confinement, effects of void ratio, buckling of FRP tube, and strain hardening of stainless steel, is proposed for CFDST. As validated by the experimental data from a wide range of literature, the proposed model is reasonable and of high accuracy.